2022
DOI: 10.1021/acs.jmedchem.2c01396
|View full text |Cite
|
Sign up to set email alerts
|

Novel Feleucin-K3-Derived Peptides Modified with Sulfono-γ-AA Building Blocks Targeting Pseudomonas aeruginosa and Methicillin-Resistant Staphylococcus aureus Infections

Abstract: The prevalence of multidrug-resistant bacterial infections has led to dramatically increased morbidity and mortality. Antimicrobial peptides (AMPs) have great potential as new therapeutic agents to reverse this dangerous trend. Herein, a series of novel AMP Feleucin-K3 analogues modified with unnatural peptidomimetic sulfono-γ-AA building blocks were designed and synthesized. The structure–activity, structure–toxicity, and structure–stability relationships were investigated to discover the optimal antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…Membrane disruptive antimicrobial peptides (AMPs), which occur naturally as part of the innate immune system, offer an opportunity to address multidrug-resistant (MDR) bacteria because of their unspecific mechanism of action, against which resistance does not occur easily. Such AMPs are however unstable in serum and most often toxic owing to their membrane disruptive amphiphilic and usually α-helical structure triggering their antibacterial effect. Their properties can be improved by sequence optimization, whereby the most versatile approach consists in introducing non-natural structural elements such as d -amino acids, non-natural residues, β- or γ-amino acids, , isopeptide bonds, or entirely non-peptidic elements such as spermine or fatty acids. , A complete redesign of AMPs is also possible in the form of dimers, cyclic or bicyclic staples, small molecules, peptoids, , foldamers, or dendrimers. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane disruptive antimicrobial peptides (AMPs), which occur naturally as part of the innate immune system, offer an opportunity to address multidrug-resistant (MDR) bacteria because of their unspecific mechanism of action, against which resistance does not occur easily. Such AMPs are however unstable in serum and most often toxic owing to their membrane disruptive amphiphilic and usually α-helical structure triggering their antibacterial effect. Their properties can be improved by sequence optimization, whereby the most versatile approach consists in introducing non-natural structural elements such as d -amino acids, non-natural residues, β- or γ-amino acids, , isopeptide bonds, or entirely non-peptidic elements such as spermine or fatty acids. , A complete redesign of AMPs is also possible in the form of dimers, cyclic or bicyclic staples, small molecules, peptoids, , foldamers, or dendrimers. , …”
Section: Introductionmentioning
confidence: 99%
“… 1 3 Such AMPs are however unstable in serum and most often toxic owing to their membrane disruptive amphiphilic and usually α-helical structure triggering their antibacterial effect. Their properties can be improved by sequence optimization, 4 7 whereby the most versatile approach consists in introducing non-natural structural elements 8 such as d -amino acids, 9 13 non-natural residues, 14 β- or γ-amino acids, 15 , 16 isopeptide bonds, 17 or entirely non-peptidic elements such as spermine 18 or fatty acids. 19 , 20 A complete redesign of AMPs is also possible in the form of dimers, 21 cyclic or bicyclic staples, 22 24 small molecules, 25 peptoids, 26 , 27 foldamers, 28 or dendrimers.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our recent late-stage peptide modification efforts, including those based on Dha, and antimicrobial peptide development, we sought to develop a rapid and facile method for peptide phosphorylation using the P Michael addition of readily available phosphites to the Dha residue, which would be a novel strategy for the screening of potential antimicrobial phosphopeptide hits (Scheme B).…”
mentioning
confidence: 99%
“…Considering the unique advantages and latent capacity of phosphorylation modification in the discovery of pharmaceutically active peptides and on the basis of our recent research interest in antimicrobial peptide drug discovery, a class of ultrashort antimicrobial active peptides were chosen as the target molecules, , to explore novel antimicrobial peptide hits by phosphorylation modification (Scheme ). It was observed that the chemically modified peptides exhibited a notable improvement in antibacterial activity against Gram-negative bacteria.…”
mentioning
confidence: 99%